La calificación registral de los títulos de expropiación en el marco del Decreto Legislativo N° 1192 - Huamanchaqui Salas, Jhosel Edwin (2022)
This academic article focuses its research on the legal figure of expropriation, the nature of the title with inscribable vocation, the registry qualification and its inscription as such in the land registry, all within the framework of Legislative Decree No. 1192. The main objective is to analyze and/or criticize the legal norm for establishing limits to the registry qualification, imposing to the registry instances the practice of the registration entry, since by mandate of this decree, they are forbidden to negatively qualify the title of an expropriation, having to be qualified as if it were a judicial mandate, even though, the title of an expropriation is of an administrative nature and should be treated given its particularities from the precedent of mandatory observance that established three years before the enactment of Legislative Decree 1192° the scope and limits of the registry qualification of administrative documents, which would protect the predictability that must exist in any legal system. In this sense, and in order to support our position, we will first develop the legal content of the expropriation institute, in order to understand its raison d'être, and then establish ourselves in the current legal regime that regulates this institute. Secondly, we will reflect on the formal principles that support our registry system, distinguishing it from other registry systems. Then, in the third chapter, after having determined that the formal principles are essential in our registry system, we will address in greater depth the principle of registry qualification, in order to determine its general scope, as well as the autonomy with which the registrar is vested and obliged in the exercise of his qualification function. Finally, we will analyze all the above, in order to establish a distant position to the limits imposed on the registry qualification as a result of this legal regime.